ANALISIS KETERLAMBATAN PENYAMPAIAN LAPORAN KEUANGAN DAN KINERJA KEUANGAN STUDI PADA PERUSAHAAN PUBLIK 1999-2005 - Tri Gunarsih (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2009)
The main objective of this study is to analyze timelines of financial statement reporting andfinancial performance in Indonesian Stock Exchange (IDX). Samples in this study are IDXpublic companies listed in 1999-2005. The research questions are tested by running ANOVAto analyze whether any differences in timelines of financial statement reporting and financialperformance between years and between size and also independent t test to analyze whetherany differences in timelines of financial statement and financial performance between industry.Timelines (KW) proxied by dummy variable, 1 if companies published financial reportingbefore 120 days after December 31 and 0 otherwise. Financial performance proxied bySales, Asset, Earning After Tax (EAT), Return on Investment (ROI), Return on Equity (ROE),and Sales Growth. The results of between year comparisons show that there are differences(increasing) between years for EAT, ROI and KW. These suggest that firm performance andtimelines of financial statement reporting are increasing over time. The results of betweensize comparisons show that there are differences between size for EAT, Sales and KW. Thebigger the size, the higher the financial performance and the timelines. The results of betweenindustry comparisons show that there are differences for Asset and EAT. Base on these variables,financial performance in service industry higher than manufacture industry.Keywords : Timelines, Financial Performance